Integrated multi-omics reveals the activated retinal microglia with intracellular metabolic reprogramming contributes to inflammation in STZ-induced early diabetic retinopathy - Lv, Kangjia; Ying, Hui; Hu, Guangyi; Hu, Jing; Jian, Qizhi; Zhang, Fang (Frontiers in Immunology, 2022)
Diabetic Retinopathy (DR) is the leading cause of visual impairment and blindness among working-age people. Inflammation is recognized as a critical driver of the DR process. However, the main retina-specific cell type producing pro-inflammatory cytokines and its mechanism underlying DR are still unclear. Here, we used single-cell sequencing to identify microglia with metabolic pathway alterations were the main source of IL-1β in STZ-induced diabetic retinopathy mice. To profile the full extent of local metabolic shifts in activated microglia and reveal the metabolic microenvironment contributing to immune mechanisms, we performed integrated metabolomics, lipidomics and RNA profiling analyses in microglia cell line samples representative of the DR microenvironment. The results showed that activated microglia with IL-1β increase exhibited a metabolic bias favoring glycolysis, purine metabolism and TAG synthesis, but less TCA. And some of these especially glycolysis was necessary to facilitate their pro-inflammation. These findings suggest that activated microglia with intracellular metabolic reprogramming in retina may contribute to pro-inflammation in the early DR.